MBE growth and characterization of ZnTe epilayers on m‐plane sapphire substrates. Issue 7 (24th March 2014) - Nakasu, Taizo; Sun, Wei‐Che; Yamashita, Sotaro; Aiba, Takayuki; Taguri, Kosuke; Kobayashi, Masakazu; Asahi, Toshiaki; Togo, Hiroyoshi
Abstract: ZnTe epilayers were grown on transparent (10‐10) oriented ( m ‐plane) sapphire substrates by molecular beam epitaxy (MBE). Pole figure imaging was used to study the domain distribution within the layer. (211)‐oriented ZnTe domains were formed on m ‐plane sapphire. The presence of only one kind of (211) ZnTe domain formed on the 2°‐tilted m ‐plane sapphire substrates was confirmed. Thus, single domain (211) ZnTe epilayers can be grown on the m ‐plane sapphire using MBE. Although differences in the crystal structure and lattice mismatch are large, precise control of the substrate surface lattice arrangement result in the formation of high‐quality epitaxial layers. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)